TLR7‐let‐7 Signaling Contributes to Ethanol‐Induced Hepatic Inflammatory Response in Mice and in Alcoholic Hepatitis - Massey, Veronica L. (Alcohol Clin Exp Res, 2018)
BACKGROUND: Toll‐like receptor 7 (TLR7) is an endosomal TLR that is activated by single‐stranded RNA, including endogenous microRNAs (e.g., let‐7b). Increased hepatic expression of TLRs, microRNAs, and inflammatory mediators is linked to ethanol (EtOH) exposure and to alcoholic liver disease (ALD). ALD invovles chronic hepatic inflammation that can progress to alcoholic hepatitis (AH), a particularly severe form of ALD. This study aimed to investigate TLR7 expression in patients with different liver disease phenotypes and in mouse liver following alcohol exposure. METHODS: Hepatic mRNA expression was determined by RNA sequencing of liver tissue from patients with liver disease or normal liver tissue. Mice were exposed to subchronic EtOH followed by administration of the TLR7 agonist imiquimod. Primary human hepatocytes were exposed to EtOH or imiquimod in vitro. RESULTS: RNAseq analysis revealed that hepatic expression of TLR7 and let‐7b microRNA, an endogenous TLR7 ligand, was significantly increased in AH patients. Hepatic expression of TLR7 and let‐7b positively correlated with hepatic IL‐8 mRNA expression. In mice, EtOH increased hepatic TLR7 mRNA expression and enhanced imiquimod‐induced expression of the pro‐inflammatory mediators TNF α, MCP‐1, and iNOS. In vitro, EtOH significantly increased hepatocyte TLR7 mRNA and the TLR7 agonist, imiquimod, induced hepatocyte expression of TNF α and IL‐8 mRNA. EtOH also increased the release of let‐7b in microvesicles from hepatocytes, suggesting that EtOH can increase the expression of both the receptor and its endogenous ligand. CONCLUSIONS: These studies suggest that increased TLR7 signaling caused by increased expression of TLR7 and its endogenous ligand let‐7b may contribute to the enhanced inflammatory response associated with AH.